2017
DOI: 10.1063/1.4998975
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution frequency variable experimental setup for studying ferrofluids used in magnetic hyperthermia

Abstract: A scanning system for specific absorption rate of ferrofluids with superparamagnetic nanoparticles is presented in this study. The system contains an induction heating device designed and built with a resonant inverter in order to generate magnetic field amplitudes up to 38 mT, over the frequency band 180-525 kHz. Its resonant circuit involves a variable capacitor with 1 nF of capacitance steps to easily select the desired frequency, reaching from 0.3 kHz/nF up to 5 kHz/nF of resolution. The device performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The minimum and maximum values for the frequency have been determined by using the smallest and largest values of the energy spacing between the levels ofĤ S . These values are given by 2 , with h being the Planck constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum and maximum values for the frequency have been determined by using the smallest and largest values of the energy spacing between the levels ofĤ S . These values are given by 2 , with h being the Planck constant.…”
Section: Resultsmentioning
confidence: 99%
“…whereŜ( j) is the spin operator acting on states defined in Eq. (2). In general, the operatorŜ( j) is written as a series of crystal field operators carrying the information about the geometry of the lattice.…”
Section: Spin-phonon Relaxation Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Cano et al [196] reported on a system based on resonant inverter with a 25 turn three layers solenoid coil with inner diameter of 5 cm generating a single frequency (206 kHz) magnetic field of 12 kAm -1 . Mazon et al [197] to improve the system reported in Cano et al [196] constructed a frequency variable system composed by a resonant inverter to generate the magnetic field over the frequency band 180-525 kHz and field amplitude up to 30.2 kAm -1 . In another improvement, Mazon et al [198] added a phase lock loop (PLL) circuit to their system to accurately tune the resonant frequency of the system during the experiments according to the inductance and capacitance of the resonant tank.…”
Section: Resultsmentioning
confidence: 99%
“…magnetic hyperthermia, several different topologies using soft-switching technique have been proposed e.g. full-bridge [196], half-bridge [197], push-pull [204] etc. These topologies usually employ metal-oxide semiconductor field-effect transistor (MOSFET) device for switching.…”
Section: Resultsmentioning
confidence: 99%